PWE-211 Longitudinal surveillance of submucosal tumours by endoscopic ultrasound: a single operator experience. (28th May 2012) - Hong, T P; Murugananthan, A U; Maqboul, N; French, J; Arroyo, Q; Chen, R Y
Abstract : Introduction: Endoscopic ultrasound (EUS) provides increasingly improved assessment of submucosal tumours (SMT). The low yield of fine needle aspiration and the benign nature of the majority of lesions leave the optimal management for smaller, asymptomatic lesions unclear as further invasive procedures or surgery may be avoidable. Longitudinal studies characterising interval change of SMT are lacking and may provide information useful in optimising management. We report the experience of a single operator in the EUS surveillance of SMTs. Methods: Patient cases were reviewed at two tertiary referral hospitals and one private hospital for patients who had serial EUS of the same lesion. EUS was performed by a single operator (RYC). For patients who had more than two EUS studies, details of the first and last were examined. Site, maximal diameter and layer of involvement were recorded. Paired data were analysed using a paired t-test with tests for correlation. Results: 73 patients with SMT had at least two EUS procedures between February 2002 and October 2011. Lesions were found in the oesophagus (14), stomach (51) and duodenum (8) with involvement of the submucosa (40), deep submucosa/muscularis propria (4) and muscularis propria (29). The range between first and last EUS was 4–80 months. The lesions varied between 4 and 50 mm with a mean maximal diameter of 15.13 mm (95% CI 12.78 to 17.49) for the first EUS and 15.73 mm (95% CI 13.36 to 18.09) for the second EUS. Paired t-test analysis between the first and last measurements show that there was no significant difference (p=0.2321), with good correlation and effective pairing (r=0.9128, p<0.0001). Conclusion: In our study of submucosal tumours smaller than 50 mm, we showed no significant change in size on surveillance EUS. Further longitudinal studies are needed to determine optimal surveillance regimen for SMTs. Competing interests: None declared.